Revitalizing Conversations: Lessons From and About the Production of Intersubjective and Intercultural Knowledge - Briones, Claudia Noemi (2021)
Fil: Briones, Claudia Noemí. Universidad Nacional de Río Negro. Instituto de Investigaciones en Diversidad Cultural y Procesos de Cambio. Río Negro; Argentina.